Estudo de sistemas reacionais enzimáticos de produto químicos com alto valor de mercado - Zanette, Andréia Fátima (2014)
The aim of this work was the enzymatic production of two high-value products to market: glyceryl monooleate (monoolein) and epoxioleic acid. The mono-olein was produced by esterification of oleic acid with solketal (D,L-,1,2 Isopropylideneglycerol) using Lipozyme RM IM lipase as biocatalyst. The reaction was carry out in supercritical conditions. First, the behavior of binary (CO2 + solketal) and ternary (CO2 + solketal + oleic acid) systems was study to predict the solubility of the system. Afterwards we performed a full factorial design with three replications at the center point where the influence of three independent variables was evaluated: temperature (33-67°C), molar ratio oleic acid:solketal (1:0.1 to 1:6,4 ) and enzyme concentration (0.1 to 13% (w/w)), keeping constant the time at 3 hour reaction and the density of the CO2 in 718 kg/m3. Finally, the reaction time was evaluated. The optimized condition corresponds to the time of 1 hour of reaction, 60°C, 1% (w/w) of enzyme concentration and molar ratio oleic acid:solketal in 1:5, reaching yields of about 70 % in the product. The second product of industrial interest, the epoxide, was obtained by epoxidation reaction of oleic acid with ethyl acetate using hydrogen peroxide as oxidizing agent. Candida antarctica B lipase was immobilized in microemulsion based organogels with cellulose hydroxylpropylmethyl cellulose (HPMC) was used as biocatalyst. The epoxidation was carried out at low pressure and in supercritical conditions, using CO2 as solvent. At ambient conditions, the reaction was optimized using a 23 factorial design with center point in triplicate, totaling 11 experiments. The following independent variables were considered: temperature (35-55°C), concentration of oleic acid (50-100 mmol/L) and amount of enzyme (0.4-0.8 mg E/mL microemulsion). The amount of H2O2 was fixed in 1.2 mL, given that in previous studies it can be seen that an excess of oxidant does not affect the structure of the enzyme. The optimized condition corresponds to the time of 48 hour reaction, 35°C, 50 mmol/L oleic acid and 0.8 mg E/mL microemulsion reaching yields about 84 % in epoxides. The study of reaction kinetics allowed us to observe that the reaction is slow, reaching 10 % in income after 1 hour of reaction. To conduct the epoxidation reaction in supercritical conditions, the behavior of the ternary system (ethyl acetate + CO2 + oleic acid) was first assessed in order to predict the solubility of the system. Then, the reaction, which did not show satisfactory results, was evaluated. An experimental design was performed and the yield remained around 10 % for all conditions evaluated. A possible negative influence for this result is the large amount of water present in the system, and CO2 under supercritical conditions has very limited solubility in aqueous systems.